2020
DOI: 10.3390/medsci8030027
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists’ Knowledge and Attitudes towards CT Radiation Dose and Exposure in Saudi Arabia—A Survey Study

Abstract: Computed tomography (CT) is a key imaging technique in diagnostic radiology, providing highly sensitive and specific information. While its use has increased dramatically in recent years, the quantity and associated risks of radiation from CT scans present major challenges, particularly in paediatrics. The fundamental principles of radiation protection require that radiation quantities be as low as reasonably achievable and CT use must be justified, particularly for paediatric patients. CT radiation knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The same study found that only 65±13.5% of radiologists had clearer comprehension of the carcinogenicity of CT scans than the patient ( 46 ). Approximately 80% of radiologists presumed that CT scans were associated with an elevated risk of developing cancer; however, only 56.5, 48.5 and 65% of the radiologists were aware of the specific risks from radiation involved in the head, chest and abdominal pediatric examinations, respectively ( 46 ). Regular, frequent and specific training courses are suggested to improve the fundamental knowledge of radiologists and other physicians regarding radiation exposure from CT scans ( 46 ).…”
Section: Specific Recommendations and Measures For Reducing X-ray Rad...mentioning
confidence: 91%
See 3 more Smart Citations
“…The same study found that only 65±13.5% of radiologists had clearer comprehension of the carcinogenicity of CT scans than the patient ( 46 ). Approximately 80% of radiologists presumed that CT scans were associated with an elevated risk of developing cancer; however, only 56.5, 48.5 and 65% of the radiologists were aware of the specific risks from radiation involved in the head, chest and abdominal pediatric examinations, respectively ( 46 ). Regular, frequent and specific training courses are suggested to improve the fundamental knowledge of radiologists and other physicians regarding radiation exposure from CT scans ( 46 ).…”
Section: Specific Recommendations and Measures For Reducing X-ray Rad...mentioning
confidence: 91%
“…The International Commission on Radiological Protection advises that the occupational dose limit for radiation exposure should be 100 mSv over a period of 5 years, with a maximum of 50 mSv in any single year ( 45 ). According to a survey performed in Saudi Arabia, a number of radiologists have limited knowledge regarding the harmfulness and carcinogenicity of X-ray radiation ( 46 ). The same study found that only 65±13.5% of radiologists had clearer comprehension of the carcinogenicity of CT scans than the patient ( 46 ).…”
Section: Specific Recommendations and Measures For Reducing X-ray Rad...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we would like to expend the use of multi pinholes techniques to more medical modalities such as Computerized Tomography (CT). In the CT procedure, there is a need for a novel configuration and operation technique to enable three-dimensional imaging of a body with decreased radiation level and preferably increasing resolution compared to current conventional CT techniques [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%